Biopesticides for New Zealands pests opportunities and challenges - O?Callaghan, M.; Wilson, M.J.; Zydenbos, S.M. (New Zealand Plant Protection, 2015)
Biopesticides can provide effective control of existing and invasive invertebrate pests and diseases impacting on New Zealands primary sector production and combat new pests emerging as a result of landuse change farming intensification and climate change While the international biopesticide market is undergoing rapid growth at present assisted by regulatory environments favourable to biopesticide registration and uptake biopesticides are not widely used in New Zealand The number of biopesticides registered under the Agriculture Compounds and Veterinary Medicines Act (Ministry for Primary Industries MPI) has slowly increased from 11 products in 1991 to 33 in 2010 with 49 registered in 2015 However only a limited number of these products are actively marketed and used by growers at present To play an increasing role in New Zealands sustainable production systems next generation biopesticides will need to have levels of efficacy comparable to currently available controls and will be able to be used by farmers with minimal change of practice This will be achieved through use of a new suite of microorganisms with broader host ranges and different modes of action from currently available microbial agents together with new cost effective production and delivery systems Efficient commercialisation of New Zealandappropriate biopesticides will also be facilitated by proposed changes to the registration process including the development of MPIs new Biological Pesticides Standard